TUGAS DAN WEWENANG LEMBAGA- LEMBAGA PENANGANAN TINDAK PIDANA KORUPSI DI INDONESIA - Junaidi Abdullah (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2014)
Corruption in Indonesia continues to increase from year to year. Corruption has become an extraordinary crime. Thus its eradication can no longer be done customarily, but it should be charged with an extraordinary way. Corruption can pose a danger to human life, because it has penetrated into various sectors such as education, health, provision of food and clothing of the people, religious life, and other social services. In Indonesia, the departments in charge of corruption are police, prosecutors and KPK. The task of the police in dealing with a criminal offense is doing the investigation. The task of attorney in dealing with corruption is also conducting an inspection, investigation and prosecution.  Then, KPK  is also  conduct  an  inspection,  investigation and prosecution. Keywords: task, authority, departments